Deposition Mechanisms in Layer-by-Layer or Step-by-Step Deposition Methods: From Elastic and Impermeable Films to Soft Membranes with Ion Exchange Properties. (25th March 2012) - Michel, Marc; Toniazzo, Valérie; Ruch, David; Ball, Vincent
Abstract : The modification of solid-liquid interfaces with polyelectrolyte multilayer films appears as a versatile tool to confer new functionalities to surfaces in environmentally friendly conditions. Indeed such films are deposited by alternate dipping of the substrates in aqueous solutions containing the interacting species or spraying these solutions on the surface of the substrate. Spin coating is more and more used to produce similar films. The aim of this short review article is to provide an unifying picture about the deposition mechanisms of polyelectrolyte multilayer films. Often those films are described as growing either in a linear or in a supralinear growth regime with the number of deposited "layer pairs". The growth regime of PEM films can be controlled by operational parameters like the temperature or the ionic strength of the used solutions. The control over the growth regime of the films as a function of the number of deposition steps allows to control their functional properties: either hard and impermeable films in the case of linear growth or soft and permeable films in the case of supralinear growth. Such different properties can be obtained with a given combination of interacting species by changing the operational parameters during the film deposition.